PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK BERBASIS PROBLEM SOLVING PADA MATA PELAJARAN KIMIA SMA POKOK BAHASAN TERMOKIMIA - Elvira Lastri; Betty Holiwarni; Abdullah Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The objective of this research was to develop the students’ activity paper in chemistry lesson subject thermochemical. The type of this research was reserach and development (R & D) with the development model 4-D. This Reseach was conducted in FKIP UR. The object of this research was the students’ activity paper based on problem solving. The data analysis technique used for this research was descriptive statistic descriptive. The descriptive analysis done by calculated the percentage of validation value. The validation done with the four aspect, such as the content properness aspect with the average score is 93,12%, the language properness with the average score is 95%, course with the average score is 86,25% and the graphical with the average score is 85,93%. Based on the result of the validator, the writer obtained the average score 90,07% which is in valid criteria, means that the development of students’ activity paper based problem solving in chemistry lesson subject thermochemical is proper to be use.Key words: Students’ activity paper, Problem Solving, Thermochemical